Communism, Nationalism, and the State: Ideological Debate between Sukarno and Isa Anshary, 1945-1970 - Adam, Yusril Fahmi; Abdurrahman, Dudung (Insaniyat: Journal of Islam and Humanities, 2024)
Sukarno as a figure nationalist-secular and Isa Anshary as a figure nationalist-Islamic political orientations has created political ideological debates in Indonesia. This research aims to analyze both figures’ thoughts based on recorded ideological debates in historical events and their compromise under ideology of communism. This historical issue was analyzed using intellectual history and political approach and was grounded in ideology and state theories. This historical research was conducted through several stages: heuristic, source criticism, interpretation, and historiography. The findings indicate that the ideological debates between Sukarno and Isa Anshary arose due to intellectual influences that led to differences in their perspectives, particularly concerning the ideology of communism. Sukarno's thoughts about communism were interpreted as a philosophy of materialism used to fight imperialism and colonialism, then his thoughts about nationalism in the form of national equality to escape the grip of colonialists, and he articulated democracy as a state concept. Meanwhile, Isa Anshary, he believes that communism is an anti-God ideology that degrades the Islamic faith, then according to him nationalism is the concept of nationalism as integration (berjamaah), and voicing Islamic ideology in the concept of the state. Furthermore, the views of Sukarno and Isa Anshary on communism also had implications for their differing stances on nationalism, the state, and political attitudes during the period leading up to the 1955 elections. In addition, the ideological debate between the two had an impact on Indonesian politics, such as political polarization and conflict in Indonesian society until the end of the Old Order.